Parenting Assistance for Early Childhood Literacy Education - Iwannudin, Iwannudin; Fatkhur Rohman; Dimas Ardiansyah; Lutvia Nur Aini; Eka Lia Paryanti; Alvy Barokah; Hana Fauziah; Nur Sangadah; Reni Wijiyati; Elva Rahayu; Siti Maryam (PT. ALHAFI BERKAH INDONESIA, 2024)
In everyday life, the most important and first environment is the family for children's lives. The family plays a very important role in efforts to develop children's personalities as well as in building a culture of literacy education for children at home and at school, because literacy education, especially for early childhood, is really needed to strengthen their education in the future. The role of the family in developing early childhood literacy is very important because it is considered the foundation for human cognitive development. However, it must be noted that developing a culture of literacy education does not mean that children are intensely and disciplined enough to learn to read, write and count like adults so that they feel forced. It is feared that this type of learning method could stress children and endanger their development. Because it is so important and there are many benefits that can be taken in educating literacy in early childhood education. We are students of the social work course (KKS) at Ma'arif University in Lampung, together with preschool teachers and the Pertiwi Kindergarten Management Board, holding parenting literacy activities for early childhood education (PAUD). With the child's parents. This is one of our appreciations as students and future educators for how to prepare the next generation to be superior and competent.